Membangun Lingkungan Sekolah yang Bebas dari Bullying untuk Mencegah Gangguan Kesehatan Mental pada Siswa Sekolah Dasar - Oktarina, Natalia Devi; Fiki Wijayanti; Zulmi Roestika Rini (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2025)
Bullying in the school environment has become one of the prominent social problems and has a major impact on the psychological development and mental health of students. Based on statistical data, in 2023, 21,241 children became victims of bullying and the highest bullying rate of 25% occurred in elementary school children. Children who experience bullying are at higher risk of experiencing mental health disorders such as anxiety, depression, social isolation, and decreased academic achievement. In the long term, these negative impacts can persist into adulthood, affecting the quality of life and mental well-being of children. Students who experience bullying at school, whether physical, verbal, or through social media (cyberbullying), often do not have access to psychological support or a safe complaint mechanism. This causes many cases of bullying to go unreported or handled properly. In addition, the involvement of parties in schools, such as teachers, other students, and parents, in preventing and handling bullying cases is often less than optimal. Bullying prevention education needs to be provided to students in elementary schools to prevent bullying in the school environment. The involvement of teachers and parents is needed to prevent bullying in the school environment. The purpose of this community service activity is to increase children's knowledge about anti-bullying and children can prevent bullying by playing games, so that they can prevent mental health disorders in school-age children.   ABSTRAK Bullying di lingkungan sekolah telah menjadi salah satu masalah sosial yang menonjol dan berdampak besar pada perkembangan psikologis serta kesehatan mental siswa. Berdasarkan data statistik, pada tahun 2023, 21241 anak menjadi korban bullying dan angka bullying tertinggi 25% terjadi pada anak sekolah dasar. Anak-anak yang mengalami bullying berisiko lebih tinggi mengalami gangguan kesehatan mental seperti kecemasan, depresi, isolasi sosial, hingga menurunnya prestasi akademik. Dalam jangka panjang, dampak negatif ini dapat bertahan hingga dewasa, memengaruhi kualitas hidup dan kesejahteraan mental anak. Siswa yang mengalami bullying di sekolah, baik fisik, verbal, maupun melalui media sosial (cyberbullying), sering kali tidak memiliki akses terhadap dukungan psikologis atau mekanisme pengaduan yang aman. Hal ini menyebabkan banyak kasus bullying yang tidak dilaporkan atau ditangani dengan baik. Selain itu, keterlibatan pihak-pihak di sekolah, seperti guru, siswa lain, dan orang tua, dalam pencegahan dan penanganan kasus bullying sering kali kurang optimal. Edukasi pencegahan bullying perlu diberikan kepada siswa di sekolah dasar perlu dilakukan untuk mencegah terjadinya bullying di lingkungan sekolah. Perlu peran serta antara guru dan orangtua untuk mencegah terjadinya bullying di lingkungan sekolah. Tujuan kegiatan pengabdian ini yaitu untuk meningkatkan pengetahuan anak tentang anti bullying dan anak dapat melakukan pencegahan bullying dengan melakukan permainan, sehingga dapat mencegah gangguan kesehatan mental pada anak usia sekolah.